Kritik Interpretasi Kelompok Pemikir Liberal Terhadap AyatAl-Qur'an Tentang Jilbab Berdasarkan Tinjauan Ulama DalamSurah Al-AḤzâb Ayat 59 - Riyadloh, Wati Nafisatur, Dr. Adian Husaini, M.A, Dr. Nirwan Syafrin Manurung, M.A (2015)
This thesis purposed to discuss interpretation from liberal thinkers group towards al-Qur'an verses about veil based on 'ulamâ reference into surah al- Aḥzâb ayat 59. There three (3) focus of discussion divided into research plan, are: those are interpretation of liberal thinkers towards al-Qur'an verses about veil, ulama's reference discourse for veil verses, and critics for liberal thinker about veil based on commentary of ulama's review. Research methods that is used is deductive one with analysis approach of ta'ṣîl, taṣwîr, tarsyîd, taṭwîr, dan tanżîr according to Islamic worldview concept. The research result shows that veil obligation is very obvious pured (ṣarîh) at surah al-Aḥzâb ayat 59, interpreted differently by liberal thinker as culture from Arabic and will not suitable to be applied now for several arguments, such as: ḥijâb supposed to be Arabic tradition in Rasulullah pbuh era only, the proof for ḥijâb is derived from solitary hadîṡ (Ḥadîṡ Âḥad) which is not valid to be used as argumentation ḥujjah syarʻe, ḥijâb is a symbol of restraint and oppression women, and ḥijâb is not a proof (evidence) symbol of faith and obedience ones. Argument and interpretation of liberal thinkers clearly erroneous, given the clarity of textual paragraph and tafsir ulama, caption sabab nuzûl, the arguments of the verses of the Qur'an and the narrations of al-Ḥadiṡ ṣaḥîḥ other scholars about the interpretation of paragraph explanation veil , restrictions female genitalia and syari'a or manners of dress, as well as the relevance and authenticity of the revelation of the verse Allah.